Using mobile health technology to improve behavioral skill implementation through homework in evidence-based parenting intervention for disruptive behavior disorders in youth: study protocol for intervention development and evaluation. Issue 1 (December 2016) - Chacko, Anil; Isham, Andrew; Cleek, Andrew; McKay, Mary
Abstract Background Disruptive behavior disorders (DBDs) (oppositional defiant disorder (ODD) and conduct disorder (CD)) are prevalent, costly, and oftentimes chronic psychiatric disorders of childhood. Evidence-based interventions that focus on assisting parents to utilize effective skills to modify children's problematic behaviors are first-line interventions for the treatment of DBDs. Although efficacious, the effects of these interventions are often attenuated by poor implementation of the skills learned during treatment by parents, often referred to as between-session homework. The multiple family group (MFG) model is an evidence-based, skills-based intervention model for the treatment of DBDs in school-age youth residing in urban, socio-economically disadvantaged communities. While data suggest benefits of MFG on DBD behaviors, similar to other skill-based interventions, the effects of MFG are mitigated by the poor homework implementation, despite considerable efforts to support parents in homework implementation. This paper focuses on the study protocol for the development and preliminary evaluation of a theory-based, smartphone mobile health (mHealth) application (My MFG) to support homework implementation by parents participating in MFG. Methods/design This paper describes a study design proposal that begins with a theoretical model, uses iterative design processes to develop My MFG to support homework implementation in MFG through a series of pilot studies, and a small-scale pilot randomised controlled trial to determine if the intervention can demonstrate change (preliminary efficacy) of My MFG in outpatient mental health settings in socioeconomically disadvantaged communities. Discussion This preliminary study aims to understand the implementation of mHealth methods to improve the effectiveness of evidence-based interventions in routine outpatient mental health care settings for youth with disruptive behavior and their families. Developing methods to augment the benefits of evidence-based interventions, such as MFG, where homework implementation is an essential mediator of treatment benefits is critical to full adoption/implementation of these intervention in routine practice settings and maximizing benefits for youth with DBDs and their families. Trial registration ClinicalTrials.govNCT01917838